Older people in the world of esport: a qualitative study - Esnard, Catherine; Haza, Marion; Grangeiro, Rebeca (Frontiers in Psychology, 2024)
The inclusion of older players in the gaming world is growing rapidly, leading to the emergence of specific categories for them at major esport events. The aim of this study is to analyze the psychological issues faced by older people when engaging with the competitive context of esport.The study was conducted in 2021 within the French association Silver Geek, which offers digital workshops using Nintendo Wii consoles to older people living in retirement homes and organizes annual amateur competitions between teams of older adults. This qualitative study involved 16 participants (eight women, eight men) aged 63 to 97 years. Semi-structured interviews were used to explore the motivations, emotional well-being, and social impact of esport on older people.The results show that older people who participate in esport are motivated by the discovery and mastery of new game skills, as well as the pleasure of performance through social comparison. All experience a psychological well-being that translates into intense positive emotions. Moreover, the esport context, whether during the pre-competition workshops or the competitions themselves, proved to be a strong vector for positive social relationships, especially with the young e-sports coaches. However, this activity had little impact on existing family relationships.This study highlights the potential of esport as a recreational activity to promote mental health and social integration in older adults. The challenge for future research is to identify the levers that will enable this activity to become a true medium for intergenerational communication.